2018
DOI: 10.1080/10428194.2018.1464158
|View full text |Cite
|
Sign up to set email alerts
|

MYC protein expression is an important prognostic factor in acute myeloid leukemia

Abstract: As new drugs targeting MYC show clinical activity in acute myeloid leukemia (AML), understanding MYC expression in AML is of critical importance. We assessed MYC protein expression by immunohistochemistry in bone marrow of patients with untreated AML (n = 265). Overall, 90% of patients demonstrated MYC overexpression and MYC immunopositivity ≤6% was associated with superior complete remission (CR) duration of 23 months versus 12 months for MYC immunopositivity >6% (p = .028). Among 241 patients at higher risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 53 publications
4
57
0
1
Order By: Relevance
“…Two previous studies have assessed the prognostic significance of MYC oncoprotein in AML patients 20,21 . In the first study performed by Mughal et al that included a total of 199 AML patients, high MYC level (IHC staining at or above median score and more than 1+ staining intensity) was associated with poor OS in patients with favorable and intermediate cytogenetic groups although it did not reach the statistical significance in the multivariate analysis adjusted by age and cytogenetic risk group 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two previous studies have assessed the prognostic significance of MYC oncoprotein in AML patients 20,21 . In the first study performed by Mughal et al that included a total of 199 AML patients, high MYC level (IHC staining at or above median score and more than 1+ staining intensity) was associated with poor OS in patients with favorable and intermediate cytogenetic groups although it did not reach the statistical significance in the multivariate analysis adjusted by age and cytogenetic risk group 21 .…”
Section: Discussionmentioning
confidence: 99%
“…790-4628; prediluted) using Ventana Discovery XT automated system. We used 5% as cut-off (calculated as MYC positive cells out of total counted blasts in the selected area with sheets of blasts) as previously reported 20 .…”
Section: Assessment Of Myc Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different murine models, either using engraftment of hematopoietic precursors over-expressing MYC or transgenic mice, demonstrated the myeloid leukemogenic activity of MYC [37] and highlighted the significance of MYC-driven abrogation of apoptosis as key molecular mechanism [41,42]. In APL, MYC cooperates with PML-RARα to accelerate the development of leukemia [43], while in AML, MYC protein expression is a poor prognostic factor, particularly in patients with high risk of relapse [44,45]. It has been reported that the inhibition of MYC in AML cell lines drastically induces cell differentiation [46], and studies in mice have demonstrated that even transient inactivation of MYC yields tumor regression [47], supporting the hypothesis that targeting MYC regulation could be a highly pursued goal to treat cancer patients.…”
Section: Myc In Myeloid Leukemiasmentioning
confidence: 99%
“…MYC encodes a transcription factor and located in the chromosome 8q24. MYC is a proto-oncogene and involved in Burkitt lymphoma and multiple myeloma and serves as a prognostic factor in acute myeloid leukemia [ 106 ]. A study showed that asthmatics have increased MYC expression in peripheral blood ILC [ 107 ].…”
Section: Literature Reviewmentioning
confidence: 99%